Home, Enslavement, and Gender: Re-encountering the Stuyvesants’s Bowery - Maskiell, Nicole Saffold (Early Modern Low Countries, 2025)
When wealthy widow Judith Stuyvesant died in her seventh decade of life, she left a will passing down her possessions to her descendants. Judith Stuyvesant’s 1684 will exposes the fraught connections between family, race, property, and power in colonial New Netherland. Her life intersected with diverse women, and her legacy was shaped by their lives as well. Among them was Mayken van Angola, an African woman who petitioned for her freedom and later married in Judith’s chapel, and Judith’s granddaughter, Anna, whose inheritance was marked by loss and violence. This article examines how wills, court petitions, and depositions offer insight into the lives of women who shaped, and were shaped by, a colonial world defined by landownership, labour, and enslavement. Through an analysis of Judith’s bowery, the family vault, and the chapel, it considers how material spaces reflected both privilege and dispossession in early New York.